2017
DOI: 10.3892/ijo.2017.4180
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the clock gene PER2 is associated with cancer development and altered expression of important tumor-related genes in oral cancer

Abstract: Recent studies have demonstrated that abnormal expression of the clock gene PER2 is closely associated with the development of a variety of cancer types. However, the expression of PER2 in oral squamous cell carcinoma (OSCC), a common malignant tumor in humans, and its correlations with the clinicopathological parameters and survival time of OSCC patients and the altered expression of important tumor-related genes remain unclear. In the present study, we detected the mRNA and protein expression levels of PER2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 40 publications
(50 reference statements)
6
43
0
Order By: Relevance
“…It is characterized by noteworthy tumor suppressor effects [11,12,25,26]. We also found previously that Per2 is expressed at lower levels in OSCC tissues and is markedly associated with the clinical stage and survival time of patients [21]. The above studies suggest that Per2 is an important tumor suppressor gene, but its antineoplastic mechanism is ambiguous, so it is of great significance to further examine its underlying mechanism.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It is characterized by noteworthy tumor suppressor effects [11,12,25,26]. We also found previously that Per2 is expressed at lower levels in OSCC tissues and is markedly associated with the clinical stage and survival time of patients [21]. The above studies suggest that Per2 is an important tumor suppressor gene, but its antineoplastic mechanism is ambiguous, so it is of great significance to further examine its underlying mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…Per2 is an important core clock gene [6,15], and existing studies have reported that Per2 expression is strikingly lower in a number of human cancers, such as gastric cancer and non-small cell lung cancer, and closely related to the development and progression of cancer [17][18][19][20]. Xiong H et al found that Per2 is expressed at lower levels in OSCC tissues and is significantly associated with the clinical stage and survival time of patients [21]. These reports suggest that Per2 is a crucial tumor suppressor gene, but its specific mechanism of tumor suppression is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of circadian clock has been linked to the development and progression of tumors (Altman et al, 2014;Yeh et al, 2014;Yu & Weaver, 2011), yet the regulation and deregulation of core clock genes in tumorigenesis is less understood. Among the clock genes, PER2 dysregulation or deletion is also frequently observed in malignancies from a broad spectrum of tissue origins, and these aberrations are associated with a more aggressive phenotype and accordingly poorer survival of the cancer patients (Liu et al, 2014;Xiong et al, 2018;Zhao et al, 2014). Of note, PER2 promoter hypermethylation is detected in endometrial cancer (Shih et al, 2010) and glioma (Fan et al, 2014), suggesting that transcriptional regulation of PER2 is pathologically relevant to tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…127 In vivo and in vitro studies have demonstrated that disruption of circadian rhythms is linked to tumour progression and mammalian tumorigenesis for several malignancies such as liver cancer, 128 oral squamous cell carcinoma, 129 gastric, pancreatic and colorectal carcinoma. 127 In vivo and in vitro studies have demonstrated that disruption of circadian rhythms is linked to tumour progression and mammalian tumorigenesis for several malignancies such as liver cancer, 128 oral squamous cell carcinoma, 129 gastric, pancreatic and colorectal carcinoma.…”
Section: Clock Genes and Cancermentioning
confidence: 99%
“…Lately, circadian disruption has been recognized as a potential independent risk factor for cancer development. 127 In vivo and in vitro studies have demonstrated that disruption of circadian rhythms is linked to tumour progression and mammalian tumorigenesis for several malignancies such as liver cancer, 128 oral squamous cell carcinoma, 129 gastric, pancreatic and colorectal carcinoma. 130 Clock genes contribute to the occurrence and development of tumours by regulating and interfering with oncogenes (c-myc), tumoursuppressor genes (P53 and P21), genes involved in the regulation of the cell cycle and vascular endothelial growth factor.…”
Section: Clock Genes and Cancermentioning
confidence: 99%